Can blood progesterone concentration identify non-pregnant buffaloes to support oestrous resynchronization? - Codognoto, Viviane M. [UNESP]; Souza, Fabiana F. [UNESP]; Salgado, Letícia C. [UNESP]; Rizzoto, Guilherme [UNESP]; Yamada, Paulo H. [UNESP]; Marques, Nayara F. S. [UNESP]; Carvalho, Nélcio A. T.; Dantas, Ariane [UNESP]; Mesquita, Ana Victória Pereira [UNESP]; Ferreira, João C. P. [UNESP]; Oba, Eunice [UNESP] (Wiley, 2022)
This study compared the plasma progesterone concentrations from pregnant and non-pregnant buffaloes to identify non-pregnant females and submit cows earlier to oestrous resynchronization. Forty-four multiparous mix-breed Murrah buffaloes were selected for the study. The cows were subjected to hormonal oestrous synchronization and separated into 4 groups, P12 (pregnant, n = 8) and P18 (n = 8) at 12 and 18 days post-insemination; NP12 (non-pregnant, n = 7) and NP18 (n = 7) at 23 and 29 days after the onset of synchronization, respectively. The embryos and blood were collected, and the plasma was separated for centrifugation and used to determine progesterone concentration. Progesterone concentration was higher in P18 than P12 (p =.02) and NP18 groups (p <.001). The steroid was also increased in the P12 group compared with NP12 (p =.031). There was no difference between NP12 and NP18 (p =.906). We conclude that the plasma progesterone concentration can be an alternative to identify earlier non-pregnant buffaloes, advancing the oestrous resynchronization or natural service to improve productivity.
Keywords: artificial insemination; bubaline; hormone; steroid